Yellow Fever, Race, and Ecology in Nineteenth-Century New Orleans - Willoughby, Urmi Engineer, 1980-; Willoughby, Urmi Engineer, 1980- (Book collections on Project MUSE., 2017)
A disease sui generis : yellow fever in world history -- Sugar fever : the rise of cane sugar and yellow fever in lower Louisiana, 1796-1850 -- Imagined immunities : ideologies of race, ecology, and disease resistance, 1840-1861 -- Reconstituting the South : built environments and public health, 1861-1878 -- Degrees of resistance : reimagining race, health, and the environment, 1878-1905 -- "Mosquito or man?" : imperialism and the rise of tropical medicine, 1878-1912 -- Epilogue : yellow fever past and present